Functionalized nanoliposomes loaded with anti survivin and anti angiogenic agents to enhance the activity of chemotherapy against melanoma by 4-pronged action - Mishra, Harshita; Mishra, Pawan Kumar; Ekielski, Adam; Iqbal, Zeenat; Jaggi, Manu; Talegaonkar, Sushama (Medical hypotheses, 2018)
Melanoma is one of the most aggressive cancers which has very low response rate and survival rate. Melanoma cells are known to be inherently resistant to the chemotherapy which results in poor outcomes and even failure of the therapy. For this reason, a better understanding of underlying mechanism of melanoma pathogenesis and resistance is required, so that more efficient and novel therapeutic strategies can be developed. Survivin is a protein which is overexpressed in melanoma cells and is known to impart resistance to them against apoptosis. Also, melanoma cells overexpress Vascular Endothelial Growth Factor (VEGF) and basic Fibroblast Growth Factor (bFGF) angiogenic growth factors which lead to aggressive angiogenesis in melanoma cells thereby making the treatment more challenging. This hypothesis presents a combinatorial approach against melanoma where an anti-survivin agent and an anti-angiogenic agent are combined with a chemotherapeutic drug and loaded in surface functionalized liposomes in order to target specific mechanisms of melanoma, thus overcoming its resistance. Thus, the study aims to overcome the resistance of melanoma cells by developing a wise combination of drugs and achieve a higher response rate in resistant melanoma model, which is usually not achieved with the existing treatment modalities.
Keywords: Liposomes; survivin; Vascular Endothelial Growth Factor A; melanom; nádory kůže; Survivin; patologická angiogeneze; Antineoplastic Agents; inhibitory apoptózy; lidé; vaskulární endoteliální růstový faktor A; Models, Theoretical; dakarbazin; fibroblastový růstový faktor 2; Angiogenesis Inhibitors; Female; Fibroblast Growth Factor 2; Skin Neoplasms; nanočástice; Nanoparticles; liposomy; Male; Cell Proliferation; ženské pohlaví; proliferace buněk; Humans; mužské pohlaví; Neovascularization, Pathologic; Inhibitor of Apoptosis Proteins; antigeny CD44; inhibitory angiogeneze; Dacarbazine; Hyaluronan Receptors; protinádorové látky; Melanoma; teoretické modely